Big Data Analytics and an Intelligent Aviation Information Management System - et. al., Catherene Julie Aarthy C, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aviation industry is grappling with two big issues: safety and performance enhancement. In the sense of big data, they would be expected to be resolved. The influence of big data on the aviation industry, as well as the creation of an aviation big data platform and information systems, are the subject of this paper. To begin, the paper investigates the relationship between big data and the growth of the smart aviation industry. The paper then discusses the fundamental concepts and context for the creation of an aviation big data platform and information system. Finally, the paper proposes a multi-layer network correlation analysis approach and uses it to investigate the range and degree of coupling in an aviation big data information system. The study concludes that aviation big data plays a critical role in the growth of the smart aviation industry, and that the creation of an aviation big data information platform and information system, as well as the use of multilayer network correlation analysis methods, will significantly improve aircraft safety and efficiency. This paper offers suggestions and countermeasures for the preparation and implementation of a national aviation big data platform and information system, as well as the development of a global aviation big data collaboration process and aviation big data technology.